The Effect of Yoga during Pregnancy on the Intensity of Labor Pain in the First Stage of Primigravida in PMB Midwives Yeti, Cianjur - Merla Amalia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Severe and prolonged labor pain can disrupt breathing, circulation, metabolism and uterine function. Pain during labor can cause an increase in blood pressure and interfere with the mother's concentration. Pregnancy can cause stress, worry and anxiety which can have physical and psychological impacts on both the mother and the fetus she is carrying. Prenatal Yoga is a complementary alternative in reducing pain during childbirth. The aim of this study was to determine the effect of yoga during pregnancy on the intensity of labor pain in the first stage of labor in primigravida at PMB Midwife Yeti, Cianjur Regency. The method used in this community service is that this community service is a type of experimental community service in the form of pre-experimental designs. The community service design is one group pretest-posttest design. 60 people. The sample in this study was 38 respondents. Bivariate analysis used the Wilcoxon test. 1st stage labor pain in 38 primigravida respondents before doing yoga average 7.26, standard deviation 1.201 and minimum pain 5 (moderate) maximum pain 9 (severe), 1st stage labor pain in 38 primigravida respondents before doing yoga mean 2.00, standard deviation 1.162 and minimum pain 0 (no pain intensity) maximum pain 4 (mild pain intensity) with p-value < α (0.000 < 0.05). The conclusion is that there is an influence of yoga during pregnancy on the intensity of labor pain in the first stage of labor in primigravida at PMB Midwife Yeti Cianjur.